2014
DOI: 10.1016/j.phpro.2014.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Laser Welding of Copper Using Multi Mode Fiber Lasers at Near Infrared Wavelength

Abstract: Due to the increasing electrification of automotive drives and the expansion of decentralized renewable energy generation, the consumption of copper for the fabrication of electrical components such as electric motors or conducting paths increases. To join these components, laser welding is more frequently used since it represents a flexible and fully automatable joining process. Because of the high thermal conductivity, the low absorption coefficient for infrared wavelength of common laser beam sources and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Consequently, these ejections as well as pores can be avoided by a proper modulation of the laser power, which counteracts the formation and stability of bubbles [83]. Other investigations confirmed the influence of the laser power and welding speed, while an important influence of the shielding gas (Helium and no shielding gas were compared) was shown [144]. The negative influence of ambient air instead of Helium can be understood qualitatively from the changes in the melt pool cross section with a narrow throat and the increased weld depth, which both increase the probability for melt ejection.…”
Section: Delicate Materials 3221 Welding Of Coppermentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, these ejections as well as pores can be avoided by a proper modulation of the laser power, which counteracts the formation and stability of bubbles [83]. Other investigations confirmed the influence of the laser power and welding speed, while an important influence of the shielding gas (Helium and no shielding gas were compared) was shown [144]. The negative influence of ambient air instead of Helium can be understood qualitatively from the changes in the melt pool cross section with a narrow throat and the increased weld depth, which both increase the probability for melt ejection.…”
Section: Delicate Materials 3221 Welding Of Coppermentioning
confidence: 90%
“…The high reflectivity complicates the laser process, so that beam sources with high intensities or wavelengths in the visible range must be used. [55,144]…”
Section: Automotivementioning
confidence: 99%
“…This produces a lot of qualitative data that, although valuable, can prove quite difficult to measure (and communicate to others). A common way to display findings from HSI is to present a single frame or sequences of frames (Fathi et al , 2010; Heider et al , 2013; Liebl et al , 2014; Moradi et al , 2013), which can be useful to describe observed phenomena, e.g. droplet shape and trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue in the copper welding process is instability when welding at low speed [1]. For a welding speed of less than 5 m/min, we typically face problems with weld instabilities such as spatter, blowholes and irregular weld seam surfaces.…”
Section: Challenge Of Copper Welding With Nir Lasersmentioning
confidence: 99%